Using Eye Movements as an Experimental Probe of Brain Function : a symposium in honor of Jean Buttner-Ennever - Buttner-Ennever, Jean A.; Kennard, Christopher; Leigh, R. John (Progress in brain research ;, 2008)
Offers examples of how eye movements can be used to address a broad range of research questions. This volume focuses on extraocular muscle, highlighting various concepts of proprioceptive control that involve even the cerebral cortex. It also illustrates implications for disorders as diverse as opsoclonus, and congenital scoliosis with gaze palsy.